(untitled) (Czech Journal of International Relations, 1967)
On days 4—5 In May 1967, an international meeting of representatives of African studies centers of European socialist countries and the Mongolian People’s Republic was held at the Prague Institute for International Politics and Economics, the aim of which was to deepen mutual cooperation and expand personal scientific contacts. Antonin Snejdarek. After analyzing the simultaneous political and economic problems of Africa, he dealt with the tasks that now face Africanist research in socialist countries in the interest of a deeper knowledge of Africa. In this context, he put forward a number of concrete proposals for closer cooperation between Africanists in socialist countries (for example, organizing regular meetings of Africanist socialist countries in other countries, organizing scientific Africanist conferences, exchange study stays of scientific and professional workers, mutual exchange of scientific books, magazines, information, visa plans, status as desired other parties etc.). The Czechoslovak proposals met with the unanimous approval of all the meeting participants.